2008
DOI: 10.1007/s00268-008-9480-5
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Homograft Tracheal Transplants in Sheep

Abstract: The results from this animal experiment reveal-contrary to data published to date-that tracheal homografts are not incorporated but absorbed. They are replaced by scar/granulation tissue that cannot secure the stability of the trachea. Therefore, further experiments with respect to the biocompatability of homografts appear to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Behrend et al have reported consistent failure of autografts [15] and allografts [16] in sheep, postulating that tracheal homografts in this animal model undergo necrosis and reabsorption, and are unavoidably destined to be replaced by a fibrous scar. On the other hand, Murakawa et al [17] obtained satisfactory results with noncircumferential transplantation of five rings in primates, but only leaving intact the membranous portion of the host and in a small number of animals.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Behrend et al have reported consistent failure of autografts [15] and allografts [16] in sheep, postulating that tracheal homografts in this animal model undergo necrosis and reabsorption, and are unavoidably destined to be replaced by a fibrous scar. On the other hand, Murakawa et al [17] obtained satisfactory results with noncircumferential transplantation of five rings in primates, but only leaving intact the membranous portion of the host and in a small number of animals.…”
Section: Discussionmentioning
confidence: 92%
“…Many previous studies have mentioned infection as a probable cause of graft failure in the sheep, [3,15,16] and it is possible that this complication is mainly…”
Section: Discussionmentioning
confidence: 96%
“…Various materials, that is, from synthetic products to biological tissues, were used for tracheal tissue reconstruction; however, previous reports with sufficiently successful outcomes are limited. Behrend et al reported in a study of homogenic tracheal transplantation in sheep that the grafts were completely absorbed and replaced by inflammatory scar tissue; thus, the stability of the trachea could not be secured [ 18 ]. A study of tissue-engineered allograft, using fibrin-hyaluronan composite gel and chondrocyte, by Kim et al showed partial success, with fine luminal contour of the regenerated site but insufficient neo-cartilage formation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%